A novel device for the study of somatosensory information processing - Holden, Jameson K.; Nguyen, Richard H.; Francisco, Eric M.; Zhang, Zheng; Dennis, Robert G.; Tommerdahl, Mark (Journal of neuroscience methods, 2012)
► A new portable sensory based tactile device is described. ► The portable device is capable of stimulating 4 finger tips independently which allows for the study of cortical–cortical interactions and their direct impact on sensory percepts. ► Conditioning stimuli have a profound, yet predictable, impact on simple tactile tests in healthy individuals. Current methods for applying multi-site vibratory stimuli to the skin typically involve the use of multiple, individual vibrotactile stimulators. Limitations of such an arrangement include difficulty with both positioning the stimuli as well as ensuring that stimuli are delivered in a synchronized and deliberate manner. Previously, we reported a two-site tactile stimulator that was developed in order to solve these problems (Tannan et al., 2007a). Due to both the success of that novel stimulator and the limitations that were inherent in that device, we designed and fabricated a four-site stimulator that provides a number of advantages over the previous version. First, the device can stimulate four independent skin sites and is primarily designed for stimulating the digit tips. Second, the positioning of the probe tips has been re-designed to provide better ergonomic hand placement. Third, the device is much more portable than the previously reported stimulator. Fourth, the stimulator head has a much smaller footprint on the table or surface where it resides. To demonstrate the capacity of the device for delivering tactile stimulation at four independent sites, a finger agnosia protocol, in the presence and absence of conditioning stimuli, was conducted on seventeen healthy control subjects. The study demonstrated that with increasing amplitudes of vibrotactile conditioning stimuli concurrent with the agnosia test, inaccuracies of digit identification increased, particularly at digits D3 and D4. The results are consistent with prior studies that implicated synchronization of adjacent and near-adjacent cortical ensembles with conditioning stimuli in impacting TOJ performance (Tommerdahl et al., 2007a,b).